Pain in older survivors of hematologic malignancies after blood or marrow transplantation: A BMTSS report. Issue 9 (5th February 2020) - Farrukh, Naveed; Hageman, Lindsey; Chen, Yanjun; Wu, Jessica; Ness, Emily; Kung, Michelle; Francisco, Liton; Parman, Mariel; Landier, Wendy; Arora, Mukta; Armenian, Saro; Bhatia, Smita; et al.
Abstract : Background: Blood or marrow transplantation (BMT) is increasingly offered to older adults with hematologic malignancies; however, their risk for severe pain is poorly understood. Using the Bone Marrow Transplant Survivor Study, the current study investigated the prevalence and predictors of pain after BMT (allogeneic or autologous) as well as its association with physical performance impairments and frailty. Methods: The cohort included 736 patients with hematologic malignancies who underwent BMT at an age ≥ 60 years at 1 of 3 transplant centers between 1974 and 2014 and survived ≥2 years after BMT; 183 unaffected siblings also participated. Study participants reported on 4 pain domains (nonminor everyday pain, moderate to severe bodily pain, prolonged pain, and moderate to extreme pain interference), and the presence of 1 or more domains was indicative of a severe and/or life‐interfering pain composite variable. Results: Overall, 39.4% of the BMT survivors reported severe pain with 2.6‐fold greater odds of reporting pain in comparison with sibling controls. Among BMT recipients, those with less education, lower incomes, and active chronic graft‐versus‐host disease had higher odds of reporting pain. In multivariable analyses, BMT survivors with pain were more likely to have impaired physical performance and were more likely to meet the frailty criteria. BMT survivors reported higher use of pain medications (17.8% vs 9.3%) and opioid pain medications (6.5% vs 2.2%) in comparison with sibling controls. Conclusions: Nearly 40% of older BMT survivors who were followed for a median of 5 years after BMT reported pain, and BMT survivors had 2.6‐fold higher odds of reporting severe, nonminor or life‐interfering pain in comparison with siblings. Abstract : Nearly 40% of older blood or marrow transplantation survivors report nonminor, life‐interfering pain with 2.6‐fold greater odds of pain in comparison with controls. Nonminor, life‐interfering pain is associated with impaired physical function, frailty, and increased prescription pain and opioid medication use.